Lack of Effect of Platelet Transfusions and Desmopressin on Intracranial Bleeding in a Patient Receiving Ticagrelor. (15th June 2015) - Maillard, Julien; Cartier Faessler, Vanessa; Fontana, Pierre; Bonhomme, Fanny
Abstract : We describe a case of a 67-year-old man who required emergency surgery for acute intracranial bleeding after having received a loading dose of aspirin and ticagrelor for an acute ST-elevation myocardial infarction. Before and during the craniocervical decompression, the assessment of platelet function was performed using the Multiplate® analyzer. Biological evaluation of platelet function was consistent with the clinical impression, suggesting that platelet transfusion and desmopressin administration in the presence of ticagrelor had very little, if any, hemostatic effect.